PUBLIC RELATIONS STRATEGY OF PT PLN (PERSERO) UP3 SIBOLGA IN BUILDING CORPORATE REPUTATION WITH STAKEHOLDERS - Afrini Yuninda Silitonga; Abdul Karim Batubara (Journal Analytica Islamica, 2026)
This study shows that PT PLN (Persero) UP3 Sibolga's public relations strategy for managing stakeholders is implemented through an integrated communication approach that combines community engagement, digital media, and strategic partnerships. This approach has proven effective in building trust, enhancing a positive image, and strengthening the company's reputation. However, various obstacles such as customer complaints, hoaxes on social media, limited human resources, and low public understanding remain challenges that need to be overcome. Therefore, it is necessary to strengthen communication capacity, optimize digital media, and continuously improve public education to ensure more effective relationships with stakeholders and maintain the company's reputation